Historical Dictionary of Spanish Cinema - Mira, Alberto (Rowman & Littlefield Publishers, 2010)
Spanish cinema is emerging as one of the most exciting, fascinating, and special cinemas in the world. Not only are others viewing Spanish films, but they are adopting Spanish producers and Spanish actors as their own. While Spanish cinema has been maturing for a long time and has been producing excellent directors, actors, and films for decades_including during the dark times of the Franco regime_only now is it winning numerous fans not only at home but also abroad. And with directors like Pedro Almod-var, actors and actresses like Javier Bardem and PenZlope Cruz, and films such as Abre los ojos and Alatriste to build upon, the outlook for Spanish Cinema appears brighter than ever. The Historical Dictionary of Spanish Cinema provides a better understanding of the role Spanish cinema has played in film history through a chronology, an introductory essay, a bibliography, and hundreds of cross-referenced dictionary entries on producers, directors, film companies, actors, and films.